The Wizard of Oz - Baum, L. Frank (Lyman Frank), 1856-1919; McKee, David (New York : Puffin Books, 2008)
After a cyclone transports her to the land of Oz, Dorothy must seek out the great wizard in order to return to Kansas.
1030L
Lexile
Accelerated Reader AR
Keywords: Gale, Dorothy -- (Fictitious character) -- Juvenile fiction; Oz (Imaginary place) -- Juvenile fiction